2000
DOI: 10.1097/00000542-200006000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil Is a Pulmonary Vasodilator in Awake Lambs with Acute Pulmonary Hypertension

Abstract: Sildenafil is a selective pulmonary vasodilator in an ovine model of acute pulmonary hypertension. Sildenafil induces pulmonary vasodilation via a NO-dependent mechanism. In contrast to zaprinast, sildenafil did not prolong the pulmonary vasodilator action of inhaled NO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0
10

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(140 citation statements)
references
References 37 publications
7
122
0
10
Order By: Relevance
“…[6][7][8][9] Sildenafil was studied in animal models of pulmonary hypertension, revealing to be a selective pulmonary vasodilator with no effects on systemic arterial pressure, enhancing the effects of inhaled nitric oxide (iNO) when given orally or intravenously. 5,10 It is a potent inhibitor of phosphodiesterase-5, which is responsible for the conversion of cGMP into GMP. The inhibition of this enzyme results in an increase of cGMP concentration in the lungs, with consequent relaxation of the smooth muscle of the vascular wall (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Sildenafil was studied in animal models of pulmonary hypertension, revealing to be a selective pulmonary vasodilator with no effects on systemic arterial pressure, enhancing the effects of inhaled nitric oxide (iNO) when given orally or intravenously. 5,10 It is a potent inhibitor of phosphodiesterase-5, which is responsible for the conversion of cGMP into GMP. The inhibition of this enzyme results in an increase of cGMP concentration in the lungs, with consequent relaxation of the smooth muscle of the vascular wall (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…66 Sildenafil proved to be a potent pulmonary selective vasodilator when used for treating PAH in animal experiments with very little fall in systemic pressure. 67 An acute vasodilatory effect on the pulmonary circulation was seen in patients with iPAH when combined with inhaled iloprost in the study by Wilkens and colleagues. 68 The fall in PVR was dose dependent in this study using intravenous sildenafil during right heart catheterisation.…”
Section: Sildenafilmentioning
confidence: 98%
“…There is genetic anticipation in familial PAH, i.e. the onset of disease occurs at an Indian Heart Journal 6401 (2012) [60][61][62][63][64][65][66][67][68][69][70][71][72][73] earlier age in successive generations. 8,9 Group 1 of Dana Point classification also includes drugs and toxins associated with development of PAH; the most notorious of these include the appetite suppressants fenfluramine and dexfenfluramine.…”
Section: Epidemiologymentioning
confidence: 99%
“…Sildenafil is a specific inhibitor of PDE5 that increases the pulmonary vasodilating effect of inhaled nitric oxide [5][6][7][8] , prevents pulmonary hypertensive crises after weaning of nitric oxide in patients with severe pulmonary hypertension 5,9 , and has its own pulmonary vasodilating effect 10,11 by increasing the GMPc levels 12 .…”
Section: Case Reportmentioning
confidence: 99%
“…In an experimental study, Weimann et al 10 showed that the pulmonary vasodilating effect of sildenafil is dose-dependent, beginning 5 minutes after its administration and reaching its maximum effect in 10 minutes.…”
Section: Case Reportmentioning
confidence: 99%